ROLE OF HOME ENVIRONMENT, PARENTAL CARE, PARENTS' PERSONALITY AND THEIR RELATIONSHIPS WITH ADOLESCENTS' MENTAL HEALTH. (7th October 2012) - Deb, S
Abstract : Background: Home environment and parent's personality are crucial for good mental health of the children and adolescents. Objective: The broad objective of the study was to examine the relationships between home environment, parental care, parent's personality and mental health of Grade XI and XII adolescents with special reference to adjustment, anxiety, self-concept and self-confidence. Methods: A group of 370 adolescents was covered in the study and data were collected by a Semi-structured Questionnaire and three standardised psychological tests. Results: About one-third (33.8%) adolescents perceived family environment to be disturbed. In this regard, statistically significant difference was found between male and female adolescents (p<0.05). A quarter (24.6%) of the adolescents thought that their parents were too much interfering in their personal affairs. Too much parental pressure for better academic performance was reported by nearly half (46.2%) of the adolescents. Overall, fathers were more likely to be considered as dominating (χ 2 (1, 740)=15.23, p<0.001) and short-tempered (χ 2 (1, 740)=7.51, p=0.006), while mothers were more likely to be considered as friendly (χ 2 (1, 740)=51.64, p<0.001). The results of multiple regression analyses indicate that parental care was associated with high self-confidence while parental pressure was associated with high anxiety. Considering father as friendly was associated with low emotional adjustment and high self-concept while mother as short-tempered was related to high anxiety. Significance/Contribution to the Field: Outcome of the study suggests sensitisation programme for parents and Life Skill Education for adolescents.